2011
DOI: 10.1517/14656566.2011.545818
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrinolytic therapy with tranexamic acid in pregnancy and postpartum

Abstract: The clinical studies suggest that tranexamic acid reduces the amount of blood loss after delivery during cesarean sections and vaginal deliveries, and reduces the requirement for blood transfusion. Tranexamic acid seems to be safe and effective in the prevention and management of bleeding during pregnancy. Further investigation and larger clinical trials with better design and methodological quality are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 58 publications
3
113
1
10
Order By: Relevance
“…The plasma fibrinogen level decreases during the third stage of labour and after placental delivery, and the level of fibrin/fibrinogen degradation products in the serum increases 1 h after child birth and remains raised in the early puerperium [8]. Hence, anti-fibrinolytics will be effective in reducing blood loss by interacting with the fibrinolytic mechanism [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma fibrinogen level decreases during the third stage of labour and after placental delivery, and the level of fibrin/fibrinogen degradation products in the serum increases 1 h after child birth and remains raised in the early puerperium [8]. Hence, anti-fibrinolytics will be effective in reducing blood loss by interacting with the fibrinolytic mechanism [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…211 Observational studies and case reports have demonstrated the successful use of tranexamic acid in the prevention and treatment of bleeding after vaginal delivery and caesarean section, with reduced amount of blood loss and requirement for transfusion. 71 In some cases, there can be shortening of the bleeding time with DDAVP, 212,213 but the effect is not reliable and it is unlikely to be sufficient as sole therapy in the context of pregnancy. If used, attention should be given to fluid restriction for the ensuing 24 hours (see section 4.9).…”
Section: What Is the Inheritance?mentioning
confidence: 99%
“…[69][70][71] If tranexamic acid is administered at the onset of established labour by intravenous injection, then it is able to exert an antifibrinolytic effect immediately, at the time of placental separation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review suggested that TA reduces the amount of blood loss after delivery and reduces the requirement for blood transfusion [6]. A Cochrane systematic review also concluded that TA decreases blood loss after vaginal and cesarean delivery [7].…”
Section: Introductionmentioning
confidence: 99%